2000
DOI: 10.1023/a:1007041909477
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Streptozotocin (STZ)-induced diabetes causes an upregulation in the expression of endothelin (ET) receptors in the rat prostate (Eur J Pharmacol 310:197, 1996). We examined the effects of insulin treatment, started 8 weeks after the induction of diabetes, on the expression and distribution of ET receptors and their respective mRNAs in the rat prostate. The densities, pharmacological properties and distribution of ET receptors in the rat prostate were examined using radioligand receptor binding and autoradiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Insulin treatment can normalize the altered prostatic weights and serum testosterone levels and molecular changes. These results suggest that the above molecular changes may be involved in the diabetesinduced prostate regression (54,99,124), which may affect male sexual response.…”
Section: T1dm and Ucodmentioning
confidence: 78%
“…Insulin treatment can normalize the altered prostatic weights and serum testosterone levels and molecular changes. These results suggest that the above molecular changes may be involved in the diabetesinduced prostate regression (54,99,124), which may affect male sexual response.…”
Section: T1dm and Ucodmentioning
confidence: 78%
“…In fact, this degenerative disease was described to affect not only sperm quality and function R S Tavares and others R14 (Bartak et al 1975, Padron et al 1984, Handelsman et al 1985, Vignon et al 1991, Baccetti et al 2002, Soudamani et al 2005, Amaral et al 2006, Scarano et al 2006, Agbaje et al 2007, Delfino et al 2007, Shrilatha & Muralidhara 2007a, Rama Raju et al 2012, Roessner et al 2012, Schoeller et al 2012a, Mangoli et al 2013 but also the hypothalamus-pituitary-gonadal axis (HPG) (Benitez & Perez Diaz 1985, Seethalakshmi et al 1987, Sudha et al 2000, Baccetti et al 2002, Lopez-Alvarenga et al 2002, Ballester et al 2004, Kim & Moley 2008, Schoeller et al 2012b, the testicular function and spermatogenesis (Cameron et al 1985, Gondos & Bevier 1995, Sanguinetti et al 1995, Sainio-Pollanen et al 1997, Ballester et al 2004, Arikawe et al 2006, Amaral et al 2009, Kianifard et al 2012, Schoeller et al 2012b, Wankeu-Nya et al 2013, Kyathanahalli et al 2014, Tavares et al 2016, the accessory organs (epididymis, prostate and seminal vesicles) (Murray et al 1981, Fukumoto et al 1993, Ikeda et al 2000, Saito et ...…”
Section: Diabetes Antidiabetic Drugs and Male Reproductive Functionmentioning
confidence: 99%
“…Studies in diabetic individuals or in diabetic conditions, provided important insights concerning the importance of insulin (its absence or excess) to the male reproductive system, with several studies reporting that the reproductive changes found in diabetic individuals could be reverted or attenuated by insulin treatment (Seethalakshmi et al 1987, Gondos & Bevier 1995, Ikeda et al 2000, Yamanaka et al 2003, Kim & Moley 2008, Singh et al 2009, Yonezawa et al 2009, Schoeller et al 2012a.…”
Section: Data From Studies In Diabetic Individuals/conditionsmentioning
confidence: 99%
“…In an additional study of similar design, treatment with insulin also reversed the upregulation of endothelin-1 binding sites in the vas deferens, apparently reflecting a homogenous population ET A receptors (Saito et al 1996 ). Subsequent studies also using a treatment design reported that treatment with insulin reversed greater expression of fibroblast growth factor-2 (also known as basic fibroblast growth factor) (Wang et al 2000 ), greater expression of transforming growth factor-β (TGF-β), and the related mRNAs, TGF-β1 and TGF-β2 (Ikeda et al 2000 ), and increased expression of endothelin receptors (about 80% ET A and 20% ET B receptors in all groups) (Saito et al 2000a ). BB/Wor rats spontaneously develop T1DM.…”
Section: Effects Of Antidiabetic Treatments On Lutd In Diabetesmentioning
confidence: 99%